INCREASE OF INCIDENCE OF CONGENITAL SYPHILIS IN SANTA CATARINA STATE BETWEEN 2007-2017: TEMPORAL TREND ANALYSIS - Julia Souza Vescovi; Fabiana Schuelter-Trevisol (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To estimate the incidence of congenital syphilis and temporal trends of the reported cases of the disease in the state of Santa Catarina between 2007 and 2017. Methods: Observational study with retrospective cohort design, with secondary data from the Injury of Notification Information System (SINAN). Linear trend test and geoprocessing were performed to verify the behavior of the cases in the period. Results: There were 2,898 reported cases of congenital syphilis in the period, with an average of 2.9 per 1,000 live births in the period. There was an exponential increase of 0.9 percentage points per year, considered statistically significant (p<0.001). There was no difference between the incidences of cases in the different regions of the State. The fatality rate was 8.5%, considering deaths from syphilis, miscarriages and stillbirths. The profile was predominant of white mothers, with low schooling and 11.8% did not perform prenatal care. For this reason, 26.9% of them had a diagnosis of syphilis at the time of delivery. Most of the pregnant women (51.9%) had inadequate pharmacological treatment and 65.1% of the partners were not treated. Conclusions: There was an exponential increase tendency in cases of congenital syphilis in the State of Santa Catarina in the period studied in all regions of the State, which reveals the failure of prenatal care, late diagnosis and inadequate treatment of the pregnant woman and her partner.